Quantitative variation in effector activity of ToxA isoforms from Stagonospora nodorum and Pyrenophora tritici-repentis - Tan, Kar-Chun; Ferguson-Hunt, M.; Rybak, K.; Waters, O.; Stanley, W.; Bond, C.; Stukenbrock, E.; Friesen, T.; Faris, J.; McDonald, B.; Oliver, Richard (AMER PHYTOPATHOLOGICAL SOC, 2012)
ToxA is a proteinaceous necrotrophic effector produced by Stagonospora nodorum and Pyrenophora tritici-repentis. In this study, all eight mature isoforms of the ToxA protein were purified and compared. Circular dichroism spectra indicated that all isoforms were structurally intact and had indistinguishable secondary structural features. ToxA isoforms were infiltrated into wheat lines that carry the sensitivity gene Tsn1. It was observed that different wheat lines carrying identical Tsn1 alleles varied in sensitivity to ToxA. All ToxA isoforms induced necrosis when introduced into any Tsn1 wheat line but we observed quantitative variation in effector activity, with the least-active version found in isolates of P. tritici-repentis. Pathogen sporulation increased with higher doses of ToxA. The isoforms that induced the most rapid necrosis also induced the most sporulation, indicating that pathogen fitness is affected by differences in ToxA activity. We show that differences in toxin activity encoded by a single gene can contribute to the quantitative inheritance of necrotrophic virulence. Our findings support the hypothesis that the variation at ToxA results from selection that favors increased toxin activity.